Complementary Medicine, Chemoprevention, and Staging of Prostate Cancer - Crawford, E. David (MedReviews, LLC, 2003)
The 13th International Prostate Cancer Update was held in Vail, Colorado, in February 2003. This article provides an overview of the high points in the areas of complementary medicine, chemoprevention, and staging that were discussed at this meeting. M. Scott Lucia, MD, addressed the use of various hormonal agents, antiproliferative or differentiating agents, antiinflammatory agents, and antioxidants in patients with prostate cancer. Wael A. Sakr, MD, provided an overview of prognostic markers for this disease. Arturo Mendoza-Valdes, MD, explored the potential role of exercise for patients with prostate cancer, and Bruce Sodee, MD, described some exciting new developments in prostate imaging. E. David Crawford, MD, discussed the ongoing Prostate Cancer Prevention Trial.